Central diabetes insipidus due to sarcoidosis - de Waard, Wolter I. Q.; van Battum, Patrick L. H.; Mostard, Remy L. M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
We describe a case of a 40-year old Caucasian male who presented with bihilar enlargement. Additional investigation revealed sarcoidosis. During hospitalization patient developed hypernatremia due to central diabetes insipidus. Central diabetes insipidus was caused by neurosarcoidosis. MRI-scan did not show abnormalities of the pituitary gland, but additional investigation showed hypopituitarism. He was treated with prednisolone, minrin and testosterone. Sodium- and testosterone levels normalised but suppletion is still required.